Has the educational use of digital technologies changed after the pandemic? A longitudinal study. - Juan-Ignacio Pozo; Beatriz Cabellos; María Del Puy Pérez Echeverría (PLoS ONE)
This longitudinal study delves into the impact of the COVID-19 pandemic on the utilization of digital tools in education, particularly focusing on the transition of classrooms into digital spaces. Three years after the lockdown, results from 144 primary and secondary teachers who also participated in a questionnaire during the lockdown indicate an expected decline in the frequency of using digital resources, particularly in attitude and assessment-related activities. Furthermore, activities centred around verbal and procedural learning continue to be teacher-centred. However, notably, experienced teachers using technologies exhibit a relative increase in the adoption of digital technologies for more student-centred activities, underscoring the significance of prior experience in effective technology integration. The study highlights the importance of teacher training to augment the incorporation of digital tools into the curriculum, promoting more effective teaching methodologies.